Time-Varying Volatility in Bitcoin Market and Information Flow at Minute-Level Frequency - Barjašić, Irena; Antulov-Fantulin, Nino (Frontiers in Physics, 2021)
In this paper, we analyze the time-series of minute price returns on the Bitcoin market through the statistical models of the generalized autoregressive conditional heteroskedasticity (GARCH) family. We combine an approach that uses historical values of returns and their volatilities - GARCH family of models, with a so-called "Mixture of Distribution Hypothesis", which states that the dynamics of price returns are governed by the information flow about the market. Using time-series of Bitcoin-related tweets, the Bitcoin trade volume, and the Bitcoin bid-ask spread, as external information signals, we test for improvement in volatility prediction of several GARCH model variants on a minute level Bitcoin price time series. Statistical tests show that GARCH(1,1) and cGARCH(1,1) react the best to the addition of external signals to model the volatility process on out-of-sample data.